The struggle to gain access: a theoretical effort to contribute to the political programme of women's right to the city - Aladro, Almendra Maribel (2025)
The right to the city, stemming from Lefebvre’s ideas, addresses the emancipation of individuals from homogenization and oppression. Analyzing 31 authors, two major groups emerge in literature: one criticizes Marxism's emphasis on social class, placing gender, race, and ethnicity on equal footing; the other focuses on the class-based tone of the right to the city, emphasizing self-management and appropriation, challenging the public-private dichotomy. The article suggests the key to understanding women's right to the city is the issue of access, viewed through the lens of Social Reproduction Theory. Access is seen as a precursor to effective rights enjoyment, closely tied to Economic, Social, and Cultural Rights. Access is crucial in understanding women's right to the city, extending beyond mere physical access to encompass self-management, appropriation, and the radicalization of the right to difference. The struggle for women's dwelling and appropriation is framed as a quest for the right to the city.